2011
DOI: 10.1007/s11270-011-0863-0
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Diethylenetriamine Pentaacetate (DTPA) and Ethylenediamine Disuccinate (EDDS) in Remediation of Selenium from Contaminated Soil by Brussels Sprouts (Brassica oleracea var. gemmifera)

Abstract: The objective of this study was to investigate the effects of adding different rates of diethylenetriamine pentaacetate (DTPA) at different concentrations (0, 0.5, 1, and 5 mmol kg −1 ) and ethylenediamine disuccinate (EDDS) at 0, 5, 7.5, and 10 mmol kg −1 on the capacity of Brussels sprouts plants to take up Se from soils contaminated with 0, 5, 10, and 15 mg kg −1 NaSeO 4 , under a greenhouse conditions. Results indicated that the application of DTPA and EDDS to Se-contaminated soils significantly affect pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Chelating agents such as EDDS, DTPA, and ethylenediaminetetraacetic acid (EDTA) are considered as a potential weapon to increase the availability of metal/metalloids for increasing the efficiency of phytoextraction. However, the utility of various chelating agents depends on the plant species and the elements to be removed [174,206,207]. On the other hand, chelator-assisted phytoextraction may induce water contamination as they increase the mobilization of toxic ions, ultimate leaching [208,209].…”
Section: Phytoextractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelating agents such as EDDS, DTPA, and ethylenediaminetetraacetic acid (EDTA) are considered as a potential weapon to increase the availability of metal/metalloids for increasing the efficiency of phytoextraction. However, the utility of various chelating agents depends on the plant species and the elements to be removed [174,206,207]. On the other hand, chelator-assisted phytoextraction may induce water contamination as they increase the mobilization of toxic ions, ultimate leaching [208,209].…”
Section: Phytoextractionmentioning
confidence: 99%
“…On the other hand, chelator-assisted phytoextraction may induce water contamination as they increase the mobilization of toxic ions, ultimate leaching [208,209]. In Brassica oleracea, Esringü and Turan [174] reported that the application of EDDS (7.5 mmol kg −1 ) and DTPA (1 mmol kg −1 ) increased Se removal by 12-20 fold from the contaminated soil.…”
Section: Phytoextractionmentioning
confidence: 99%
“…Lot of research work has been done so far to better understand the application of this green technology approach for seleniferous soil treatment under various environments. Study conducted by Esringü and Turan ( 2012 ) found that adding ethylenediamine disuccinate and diethylenetriamine pentaacetate (synthetic chelating agents)with Se-contaminated soil helped soil particles to free Se by making it more readily available for roots uptake. As a result, Brussels sprouts increase Se elimination by 12- to 20 times.…”
Section: Se Remediation Technologiesmentioning
confidence: 99%
“…Currently, there are no inexpensive and easily implemented technologies for remediation of selenium contaminated groundwater. Methods to remove selenium from water and groundwater include phytoremediation (Esringü and Turan, 2012), biological treatment (Hageman et al, 2013), ion exchange, evaporation, chemical treatment and filtration (Bond, 2000) and permeable reactive barriers (PRB) (Zhang et al, 2008). All of these methods with the exception of using PRB are active treatment technologies that have significant capital costs, create waste streams, can expose workers to the contaminant and have significant long-term operational costs (Moore, 2003;Moore et al, 2004;Naftz et al, 2002).…”
Section: -mentioning
confidence: 99%